Pengaruh Pemberian Galaktomanan dari Daging Kelapa Lokal (Cocos nufitera L) terhadap Kadar Glucagon Like Peptide-1 (GLP-1) pada Tikus Wistar Jantan yang Hiperkolesterolemia - Inayatul Aulia; Achmad Subagio; Aris Prasetyo (Pustaka Kesehatan, 2014)
Hypercholesterolemia is a condition characterized by high cholesterol concentration in blood. This is a risk factor for many diseases. Glucagon Like Peptide-1 (GLP-1) is an incretin hormone that affects cholesterol and other diseases with hypercholesterolemia as a risk factor. Drug that widely used for hypercholesterolemia is simvastatin which can increase GLP-1. GLP-1 also can be increased by high fibrous foods consumption, one of which is galactomannan which can be found in coconut as much as 61%. This study aimed to determine the effect of galactomannan on GLP-1 and compared with simvastatin. Wistar rats were induced into hypercholesterolemia and than treated with galactomannan 70 mg/200gBW/day and 140 mg/200gBW/day and simvastatin 0,1 mg/200gBW/day. After 28 days, GLP-1 levels was measured. The result showed that GLP-1 in 140 mg/200gBW/day group was the highest and in 70 mg/200gBW/day group was the lowest. Data analysis revealed no significant difference between 140 mg/200gBW/day and simvastatin group. In conclusion, galactomannan 140 mg/200gBW/day had the same potency as simvastatin 0,1 mg/200gBW/day.   Keywords: Hypercholesterolemia, GLP-1, Galactomannan, Simvastatin